PENGARUH EKSTRAK KULIT BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) TERHADAP OVARIUM MENCIT MODEL ENDOMETRIOSIS - sagita candra puspitasari (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2017)
Endometriosis occurs when one of the normal tissues grows ectopically on the organs of the body other than the uterus. One of the mechanisms of infertility associated with endometriosis is a change in immune system function that affects the ovarian follicle which causes an increase in granulosa cells in the ovarian follicle endometriosis patients. The red dragon fruit is one of the plants capable of inhibiting NF-ÎºB secretion of cytotine from endometriosis. This study aims to study the effect of red dragon fruit extract on the ovaries of mice of endometriosis model. 12 samples of female mice divided into 2 groups consisting of positive control group and treatment group used as endometriosis for 14 days, then the next 14 days positive group is given solution Na-CMC 0,5%, while treatment group given dose 0,25 mg / gram BB. This research type is true experimental by using randomized post test only control experimental group design. The results of this study indicate that there is a significant difference in the number of granulosa cell apoptosis between groups. Provision of extract dragon fruit peel in mice model of endometriosis can decrease the number of granulosa cell apoptosis with significant result P <0,05. Keywords : extract of hylocereus polyrhizuspeel, endometriosis, granulose cell apoptotic